Genomic and Physiological Characterization of Bacilli Isolated From Salt-Pans With Plant Growth Promoting Features - Petrillo, Claudia; Castaldi, Stefany; Lanzilli, Mariamichela; Selci, Matteo; Cordone, Angelina; Giovannelli, Donato; Isticato, Rachele (Frontiers in Microbiology, 2021)
Massive application of chemical fertilizers and pesticides has been the main strategy used to cope with the rising crop demands in the last decades. The indiscriminate use of chemicals while providing a temporary solution to food demand has led to a decrease in crop productivity and an increase in the environmental impact of modern agriculture. A sustainable alternative to the use of agrochemicals is the use of microorganisms naturally capable of enhancing plant growth and protecting crops from pests, known as Plant-Growth-Promoting Bacteria (PGPB). Aim of the present study was to isolate and characterize PGPB from salt-pans sand samples with activities associated to plant fitness increase. To survive high salinity, salt-tolerant microbes produce a broad range of compounds with heterogeneous biological activities that are potentially beneficial for plant growth. A total of 20 halophilic spore-forming bacteria have been screened in vitro for phyto-beneficial traits and compared with other two member of Bacillus genus recently isolated from the rhizosphere of the same collection site and characterized as potential biocontrol agents. Whole-genome analysis on seven selected strains confirmed the presence of numerous gene clusters with PGP and biocontrol functions and of novel secondary-metabolite biosynthetic genes which could exert beneficial impacts on plant growth and protection. The predicted biocontrol potential was confirmed in dual culture assays against several phytopathogenic fungi and bacteria. Interestingly, the presence of predicted gene clusters with known biocontrol functions in some of the isolates was not predictive of the in vitro results, supporting the need of combining laboratory assays and genome mining in PGPB identification for future applications.